Pengaruh Kehandalan Pelayanan BSI (Konfirmasi Sebelum Menggunakan Produk Atau Jasa) Terhadap Teori Expectancy-Disconfirmation - Murni Nia; Murniati Murniati; Ilhamurrahman M Hubaib; Suwalni Suwalni (Edupreneurship: Jurnal Pendidikan Ekonomi, 2026)
The study “The Effect of BSI Service Reliability (Confirmation Prior to Using a Product or Service) on Expectancy-Disconfirmation Theory” by Suwalni (A1A122067) aims to determine the effect of the service reliability dimension, particularly the practice of confirming product or service information prior to use, on student customer satisfaction, and to interpret the findings through the Expectancy-Disconfirmation Theory. This study used a quantitative methodology with a survey method. A sample of 35 respondents was selected using accidental sampling from a population of 405 students of the Economic Education Study Program, Faculty of Teacher Training and Education, Halu Oleo University, who are customers of Bank Syariah Indonesia (BSI). Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with the assistance of SPSS. The results show that the five service quality dimensions (tangibles, reliability, responsiveness, assurance, and empathy) simultaneously have a significant effect on student satisfaction, with an F-count of 11.608 and an R² of 0.667. Partially, the reliability variable obtained a t-count of 2.312 with a significance of 0.028, indicating a significant effect, but with a negative regression coefficient of -0.366. This finding is interpreted through the Expectancy-Disconfirmation Theory, in which students with a better understanding of Islamic banking operations hold very high expectations regarding service accuracy and consistency, so that even minor gaps between expectation and actual performance produce a proportionally larger negative effect on satisfaction than other dimensions.